Implikasi Perubahan Kebijakan Merek Non-Use Terhadap Penghapusan Merek Terdaftar - Fallonne, Anitia Emalia; Widodo, Selamat (IAIN Langsa, 2025)
The Constitutional Court issued Decision Number 144/PUU-XXI/2023. The decision contains an extension of the time limit for non-use trademarks from 3 years to 5 years and adds the provision of force majeure to the provision of valid reasons. This policy certainly has an impact on non-use trademark holders to maintain their brands and third parties have to wait longer. This research aims to analyze how the implications of non-use trademark policy changes on the elimination of registered trademarks based on the perspective of justice and the principle of national treatment. The research method used is normative juridical. The results of the study concluded that based on the perspective of justice, the implications of changes in the non-use trademark deadline policy on the elimination of registered trademarks in Indonesia have a major impact in providing justice for trademark owners, especially micro, small and medium enterprises (MSMEs). Based on the principle of national treatment, the implications of this policy change strengthen the fairness of trademark law in Indonesia by providing equal protection for domestic and foreign trademark owners, while maintaining the rights of domestic and foreign third parties. And maintaining compliance with international commitments contained in TRIPs.